MICROBIOLOGICAL MAIN CHRACTERISTICS OF VIRAL HEPATITIS (World Bulletin of Public Health, 2022)
The goal of this is to determine the etiological structure of hepatitis B, the level and, in part, the clinic of combined (mixed) forms of hepatitis B in children